2020
DOI: 10.1186/s13223-020-0402-x
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic hypersensitivity and adverse reactions: management and implications in clinical practice

Abstract: Background: Studies have shown the discrepancy between self-reported antibiotic allergies and true allergies. Inaccurate reporting of antibiotic hypersensitivities can limit treatment options and result in use of more expensive antibiotics and contribute to resistance. Methods:This retrospective cohort chart review obtained data on 16,515 patients after obtaining IRB approval. Patients who had an antibiotic adverse reaction were identified, recorded, and their management reviewed. 7926 patients were selected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 18 publications
1
21
0
Order By: Relevance
“…Patients treated with antibiotics experience a variety of adverse events including gastrointestinal distress, rash, anaphylaxis, and Stevens-Johnson syndrome. 31,35 A 2020 study of antibiotic-related adverse reactions found that 11% of patients treated with antibiotics in an outpatient setting experienced adverse reactions. 35 The study was a retrospective chart review, therefore, the model assumes that all adverse reactions reported in the study were significant enough to require follow-up care, though this may be an overestimation that is accounted for in the sensitivity analysis.…”
Section: Adverse Eventsmentioning
confidence: 99%
“…Patients treated with antibiotics experience a variety of adverse events including gastrointestinal distress, rash, anaphylaxis, and Stevens-Johnson syndrome. 31,35 A 2020 study of antibiotic-related adverse reactions found that 11% of patients treated with antibiotics in an outpatient setting experienced adverse reactions. 35 The study was a retrospective chart review, therefore, the model assumes that all adverse reactions reported in the study were significant enough to require follow-up care, though this may be an overestimation that is accounted for in the sensitivity analysis.…”
Section: Adverse Eventsmentioning
confidence: 99%
“…[31][32][33][34] Adverse Events Patients treated with antibiotics experience a variety of adverse events including gastrointestinal distress, rash, anaphylaxis, and Stevens-Johnson syndrome. 31,35 A 2020 study of antibiotic-related adverse reactions found that 11% of patients treated with antibiotics in an outpatient setting experienced adverse reactions. 35 The study was a retrospective chart review, therefore, the model assumes that all adverse reactions reported in the study were significant enough to require follow-up care, though this may be an overestimation that is accounted for in the sensitivity analysis.…”
Section: Antibiotic Typementioning
confidence: 99%
“…31,35 A 2020 study of antibiotic-related adverse reactions found that 11% of patients treated with antibiotics in an outpatient setting experienced adverse reactions. 35 The study was a retrospective chart review, therefore, the model assumes that all adverse reactions reported in the study were significant enough to require follow-up care, though this may be an overestimation that is accounted for in the sensitivity analysis. Patients experiencing more mild adverse events are more likely to seek follow-up care in an outpatient setting, while emergent reactions like anaphylaxis and Stevens-Johnson syndrome are treated in the ED.…”
Section: Antibiotic Typementioning
confidence: 99%
See 2 more Smart Citations